Evaluation of Non-Pharmacological Remedies Adopted By The Patients with Diabetes Mellitus Type 2 - Hasan, Insia; Batool, Syeda Ramsha; Dars, Jawed Akbar; Batool, Rabisa; Ahmad, Syed Masroor; Afridi, Muhammad Iqbal (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine the different types of non-pharmacological remedies adopted by the patients with type 2 diabetes.Study Design: Cross-sectional study.Place and Duration of Study: Jinnah Postgraduate Medical Centre, Karachi from Oct 2018 to Nov 2019.Methodology: A total of 280 type 2 diabetes patients were enrolled in the study. All patients with multiple comorbidities and type 1 diabetes were excluded from the study. A pre-designed questionnaire was used to collect data using face to face interviews. The questionnaire was related to the biodata of the patients and the use of non-pharmacological measures to control the diabetes. Data was analyzed by using SPSS version 24.Results: The mean age of the patients was 54.7 ± 9.77 years. About 256 (91.4%) stated that they used non-pharmacological measures along with their medications to control diabetes. Most of the patients 248 (96.8%), were only on dietary modifications; regular exercise 82 (32%) and various types of medicinal herbs/spices were used by 65 (25.3%) patients. Regular walking was the most common exercise chosen by patients and most of them preferred to walk 30 minutes daily. Out of 241 (97%) patients altered their diet to low carbohydrates and rice consumption, increased use of fruits and vegetables 29 (11.6%) and cereals by 24 (9.6%) patients.Conclusion: The study concluded that patients were highly inclined towards the use of non-pharmacological measures to control their illness.